АЎЫЛЛЫҚ ОРЫНЛАРҒА ГЕОГРАФИЯЛЫҚ ТӘРЕПТЕН СЫПАТЛАМА - Утепова, Г.Б.; Узақбаев, Қ.К. (FAN va JAMIYAT, 2025)
This article provides a geographical description of rural areas and a scientific assessment of characteristics inherent to rural territories.